Pengaruh Dosis Pupuk Kotoran Ternak Ayam Terhadap Pertumbuhan dan Produksi Rumput Brachiaria humidicola pada Pemotongan Pertama - Maria Erviana Kusuma (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2015)
The aims of this research were to determine the effect dosage of chicken manure and want to know the dosage of chicken manure that give the best result for growth and production of Brachiaria humidicola.